Epidemiology of herpes simplex and varicella zoster virus in cerebrospinal fluid of patients suffering from meningitis in Iran. (July 2020) - Pormohammad, A.; Goudarzi, H.; Eslami, G.; Falah, F.; Taheri, F.; Ghadiri, N.; Faghihloo, E.
Abstract: From the early 18th century that "meningitis" outbreak was firstly recorded in Geneva, it is one of the alarming health problems worldwide. Different infectious risk factors may contribute to the progression of meningitis. Herpes simplex virus (HSV) and Varicella-zoster virus (VZV) are just some noticeable risk factors among many involved in the progression of this disease. In this study, 415 meningitis suspected patients were recruited with some symptoms, such as fever, headache, nausea or vomiting, seizure, rash, dizziness from four different hospitals of Iran and molecular examinations of samples were performed by using specific primers of HSV½ and VZV via real-time PCR. Out of 415 included patient 41 (9.8 %) were VZV and six (1.4 %) cases were HSV ½ positive. Fever was the most frequent symptom by 315 (76 %) of patients with median temperature of 38 °C in all included patients. The median WBS counts of CSF in VZV positive, HSV½ positive, and all included cases were 1567 × 10 6 /L, 1257 × 10 6 /L, and 766 × 10 6 /L (range 0-21200), respectively. In conclusion, as the rate of VZV infection was high among children patients and it was associated with the absence of vaccination program for chickenpox in Iran, we suggested that VZV is one of the plausible hallmarks in meningitis.